Calycosin Alleviates Sepsis-Induced Acute Lung Injury via the Inhibition of Mitochondrial ROS-Mediated Inflammasome Activation - Xia, Yu; Cao, Yuanbao; Sun, Yao; Hong, Xiuying; Tang, Yingyan; Yu, Juan; Hu, Hongjuan; Ma, Wenjia; Qin, Kailun; Bao, Rui (Frontiers in Pharmacology, 2021)
Sepsis-induced acute lung injury (ALI) culminates in multiple organ failure via uncontrolled inflammatory responses and required effective treatment. Herein, we aimed to investigate the effect of Calycosin (CA), a natural isoflavonoid, on sepsis-induced ALI. CA attenuated lipopolysaccharide (LPS) and cecal ligation and puncture (CLP)-induced structural damage and inflammatory cell infiltration in lung tissues by histopathological analysis. CA significantly reduced lung wet/dry ratio, inflammatory cell infiltration in bronchoalveolar lavage fluid and myeloperoxidase activity. Moreover, CA improved survival of septic mice. CA also substantially inhibited interleukin (IL)-1β and IL-18 levels, cleaved Caspase1 expression and activity in lung tissues. Additionally, CA markedly suppressed oxidative stress by increasing levels of superoxide dismutase and glutathione while decreasing malondialdehyde. In vitro assay showed that CA significantly inhibited LPS-induced IL-1β and IL-18 levels, cleaved Caspase1 expression and activity in BMDMs. Moreover, CA blocked the interaction among NLRP3, ASC and Caspase 1 in LPS-treated cells. CA markedly reduced mitochondrial ROS levels. Significantly, compared with CA treatment, combination of CA and MitoTEMPO (mitochondria-targeted antioxidant) didn’t further reduce the IL-1β and IL-18 levels, cleaved Caspase1 expression and activity as well as decreased mitochondrial ROS levels. Collectively, the inhibition of mitochondrial ROS-mediated NLRP3 inflammasome activation contributes to the protective effects of CA, which may be considered as a potential therapeutic agent for septic ALI.